An exploration of the interaction between integration and discipline in a former model C school in East London - Smulders, Heidi (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
Educators work in dynamic contexts which reflect the social and political circumstances of the time. Since the African National Congress was elected to govern in 1994, educators working in former Model C schools have been particularly affected by changes in the law regarding education. The South African Schools Act of 1996 prohibited discriminating in any way against learners applying for admission to schools. This has resulted in cultural and racial integration occurring at all former Model C schools. The use of corporal punishment in schools was also prohibited in 1996. This study attempts to obtain an understanding of the interaction between integration and discipline which was identified at a particular Model C school in East London. It also aims to obtain educators' understandings of the challenges of integration and discipline at this school. Following an in-depth pilot study of the school's detention records for 1998, twenty-two out of sixty educators at the school participated in the research by responding to written questionnaires. It is argued that two different approaches to integration are presently used by educators. These are identified and discussed, namely assimilatory education and multicultural education. The need for consistency between educators in their approaches to integration and discipline is also addressed.
Keywords: School discipline -- South Africa -- Eastern Cape -- Case studies; Multicultural education -- South Africa -- Case studies